Pengaruh Keterampilan Kerja, Disiplin Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Gethuk Take Tawangmangu - Hesti Nurhasanah; Sutarno (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the significance of the influence of work skills, work discipline, and work motivation on the work productivity of Gethuk Take Tawangmangu employees. The type of data used in this study is quantitative data. The data source used is primary data. The population of this study is Gethuk Take Tawangmangu employees. Data collection was carried out using a survey method through questionnaires distributed to 35 respondents. The data analysis method in this study is multiple linear regression analysis using SPSS as a tool for data processing. The results of the study indicate that work skills and work discipline have a significant effect on the work productivity of Gethuk Take Tawangmangu employees while work motivation does not have a significant effect on the work productivity of Gethuk Take Tawangmangu employees. The R2 value of 72.8% means that the work productivity of Gethuk Take Tawangmangu employees can be explained by the variables of work skills, work discipline and work motivation while the remaining 27.2% means that the work productivity of Gethuk Take Tawangmangu employees is explained by other variables such as work environment, compensation, workload and so on which are not examined in this study.